Understanding of Student Self-Management in Mathematics Education at UNU Pasuruan - Rachmawati, Titik; Farizhi, Akhmad Salman; Mukhsinin, Hidayatul (Journal of Mathematical Pedagogy (JoMP), 2023)
This research aims to understand how students manage time, plan, motivate, and respond to difficulties in the context of mathematics learning. The research methods used include surveys, interviews and documentation analysis. The research results show that students who are successful in learning mathematics tend to have better self-management skills. This research provides insight into the role of self-management in students' success in understanding mathematical concepts and provides a basis for developing learning strategies that can improve students' self-management skills. The conclusions of this research is provide a better understanding of the factors that influence the implementation of student self-management in the context of mathematics education, as well as providing direction for the development of more effective learning approaches.